2011
DOI: 10.1007/s13277-011-0223-0
|View full text |Cite
|
Sign up to set email alerts
|

The expression and clinical significance of CLIC1 and HSP27 in lung adenocarcinoma

Abstract: The purpose of this research was to study the roles of chloride intracellular channel protein 1 (CLIC1) and heat shock protein 27 (HSP27) in the clinical pathology of lung adenocarcinoma and to explore whether the expression of CLIC1 and HSP27 can be used as independent factors for the prediction of recurrence and prognosis after radical resection of lung adenocarcinoma. One hundred and three paraffin sections of lung adenocarcinoma tissues were collected, and the expression of CLIC1 and HSP27 was detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…Interestingly, HSP27 expression levels have been described as a discriminator between SqCC and normal bronchial epithelium, squamous metaplasia, atypical hyperplasia, and carcinoma in situ (49). However, HSP27 has also been detected in ADC by IHC (50). We found HSP27 expression in both, SqCC and ADC, but significantly more often in SqCC specimens (p Ͻ 0.001).…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, HSP27 expression levels have been described as a discriminator between SqCC and normal bronchial epithelium, squamous metaplasia, atypical hyperplasia, and carcinoma in situ (49). However, HSP27 has also been detected in ADC by IHC (50). We found HSP27 expression in both, SqCC and ADC, but significantly more often in SqCC specimens (p Ͻ 0.001).…”
Section: Discussionmentioning
confidence: 59%
“…At present, CLIC1 has been found to be closely related to many kinds of tumors. Several studies have shown that CLIC1 is expressed at a low level in normal gastric tissues and highly expressed in GC tissues [14-16]. It has also been found that the expression of CLIC1 in GC is closely related to the invasion and metastasis of lymph nodes and the infiltration of peripheral nerves, suggesting that CLIC1 is a potential tumor marker [7].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its ubiquitous expression, CLIC1 has regularly been shown to be up-regulated in patients with malignant tumors of the brain, liver, lung, ovaries and gastro-intestinal tract and in many of these malignancies, CLIC1 expression correlates with aggressive disease and poor outcome (12, 1922). In addition, CLIC1 has been shown to be over-expressed in the tumor vasculature indicating that CLIC1 plays an important role in the different aspects of tumor growth and metastasis (10).…”
Section: Discussionmentioning
confidence: 99%
“…CLIC1 is overexpressed in the tumor vasculature and frequently up-regulated in patients with cancers originating from the breast, lung and liver (1012). Increasing concentrations of CLIC1 have also been detected in the serum of patients with aggressive ovarian cancer suggesting that CLIC1 could be useful as a tumor marker (13).…”
Section: Introductionmentioning
confidence: 99%